FACTORS DRIVING PUBLIC SERVICE INNOVATION IN THE PEKAN KITA (PEKA) APPLICATION IN PEKANBARU CITY - Rahman, Khairul; Khotami, Khotami; Setiawan, Riski; Safitri, Eka Anjani; Otman, Zaheruddin Bin (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
The government is obliged to provide a means of complaint to manage public service complaints, and in each facility there must be information on the grievance mechanism that is implemented properly, quickly, appropriately and can be accounted for. The Pekanbaru City Government in responding to various demands and community needs for more responsive and effective services in handling public complaints has innovated public services, namely through the Pekan Kita Application (PEKA). The PEKA application is a means of public complaints to local governments, mobile-based and web-based for handling public complaints against public services that can be immediately handled by the Pekanbaru City Government. This study aims to determine the driving factors of public service innovation in the Pekan Kita (PEKA) application. This research uses qualitative methods. Data collection techniques include interviews, observation and documentation. The results of the study found that there are several factors driving public service innovation in the Pekan Kita (PEKA) application in Pekanbaru City, namely leadership factors, integrated services, community participation and involvement, commitment, and resources. Each context of public service innovation by local governments can have its own unique challenges and factors, so innovation strategies need to be adapted to local circumstances.gb777